Math, asked by xxdraina27, 10 months ago

6(1 - 4x) + 7(2-5x) = 53 Please help solve the eqaution

Answers

Answered by arunaingale2018
0

Answer:

6-24x + 14-35x=53

6+14 -24x-35x= 53

20-59x=53

-59x=53-20

-59x=33

x= -33/59

hope it helps you,

plzz mark me as brainlist.

Answered by mehreennaikoo123
2

Simplify both sides of the equation.

6(1−4x)+7(2−5x)=53

(6)(1)+(6)(−4x)+(7)(2)+(7)(−5x)=53(Distribute)

6+−24x+14+−35x=53

(−24x+−35x)+(6+14)=53(Combine Like Terms)

−59x+20=53

−59x+20=53

Step 2: Subtract 20 from both sides.

−59x+20−20=53−20

−59x=33

Step 3: Divide both sides by -59.

 \frac{ - 59x}{ -5 9}  =  \frac{33}{ - 59}  \\  \frac{ - 33}{59}

Similar questions